Complications in early pregnancy. Issue 1 (January 2015) - Graham, Anna; Devarajan, Sangeetha; Datta, Shreelata
Abstract The pregnant woman presents a diagnostic challenge as physiological, anatomical and biochemical changes of pregnancy may mask symptoms and signs, as well as the pregnancy itself being the source of the problem. The pathologies occurring in early pregnancy are common but some may be life threatening and it is therefore essential to promptly diagnose and treat complications to achieve the best fetal and maternal outcomes. This review considers the common clinical problems that occur in early pregnancy, including the common clinical and diagnostic features of obstetric and non-obstetric related causes, treatment methodologies and implications.